Identification of pathogenesis pathway in basal-like breast cancer based on mutant p53 protein and topoisomerase-IIα expression (Faculty of Medicine Universitas Indonesia, 2014)
Background: Basal-like breast cancer is difficult to treat with standard regimen therapy, because it doesnât express hormone receptors or epidermal growth factor receptors. Identification of oncogenesis pathway is expected to find molecules which can be used as target for therapy. One candidate molecule is topoisomerase-IIα whose expression is regulated by p53. This study aimed to compare the expression of mutant p53 proteins and topoisomerase IIα in basal-like and non basal-like breast cancer, and to determine the association between mutant p53 proteins and topoisomerase IIα in basal-like group. Methods: The samples were 40 formalin fixed paraffin embedded tissues from verified triple negative breast cancer tissue. The samples were divided into 2 groups, basal-like and non basal-like breast cancer, based on cytokeratin - 5 (CK-5) expression. Mutant p53 proteins and topoisomerase IIα were stained using immunohistochemistry method, scored and compared. Statistical test used SPSS software version 16 for descriptive statistics, kappa test, normality test, comparison of two mean, and categorical comparison. Results: Median (min-max) of mutant p53 protein expression in basal-like group was 21 (0-100), the non basal-like group was 2 (0-80), p = 0.061. Min-max of topoisomerase IIα in basal-like group was 263 (15-492), non basal-like group was 262 (0-481), p = 0.409. There was an association between mutant p53 positivity with breast cancer subtype (p = 0.027) and between mutant p53-topoisomerase IIα coexpression with breast cancer subtype (p = 0.018). Conclusion: Co-expression of mutant p53 with topoisomerase IIα has the role in one of the pathway of basal-like breast cancer pathogenesis.